Amish midwives : three stories - Clipston, Amy; Gray, Shelley Shepard; Long, Kelly (Zondervan, 2021)
Bundles of blessing: Kristina Byler is lost in grief after the death of her husband and finds purpose in being a midwife. When her ex-boyfriend moves back to the community they both have issues to face before moving on.